The need to unmask lurking false friends: Sustainability is a state, not a process! - a reply to Fernandez et al. (2012) - Monjeau, Jorge Adrian (2013)
Monjeau (2010, p. 117) concluded that “a possible way out from conservation crossroads might consist in being able to distinguish friends from dangerous enemies” and that conservation in Latin America is “full of Trojan horses”. This was in reference to the quantity of deceits hidden behind certain concepts, which although offered as promising solutions for conservation are also highly ambiguous. One such concept is “sustainable development”